2001
DOI: 10.29244/jitl.2.2.8-17
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Chemical Properties and Application as Acid Soil Amendment of Pretreatment Center Slag and Other Slags

Abstract: Chemical properties of Pretreatment center slag (PTC-slag) were analyzed and compared to those of converter slag (C slag) and blast furnace slag (BF slag). PTC slag had a high EC value as well as citric acid soluble P and contained more Ca, Si, P, K, and Na but less Mg and Fe than C slag. Compared to BF slag, PTC slag contained more Fe, Ca, Mg, P, Mn, and Na but less Si, Al, and K. Although neutralizing value of PTC slag was lower than that of C slag, its ability to neutralize soilacidity was markedly higher. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…In the treatments with the use of BFS slag, this increase was higher due to the higher chemical activity of BFS slag. In addition, Suwarno et al (2001) found that both types of slag significantly increased soil pH; exchangeable Ca, and Mg in Andisol.…”
Section: Resultsmentioning
confidence: 91%
See 3 more Smart Citations
“…In the treatments with the use of BFS slag, this increase was higher due to the higher chemical activity of BFS slag. In addition, Suwarno et al (2001) found that both types of slag significantly increased soil pH; exchangeable Ca, and Mg in Andisol.…”
Section: Resultsmentioning
confidence: 91%
“…Similarly, Suwarno et al (2001) found that the magnitudes of the effects of the two slags were different.…”
Section: Resultsmentioning
confidence: 93%
See 2 more Smart Citations